"Hidden Behind the Supplement". Issue 3 (1st November 2014) - DUSCHINSKY, ROBBIE
Abstract In contrast to functionalist explanations of themes of purity and impurity as an expression and affirmation of the social order (e.g. Emile Durkheim, Mary Douglas), Giorgio Agamben considers purity and impurity as comparisons of phenomena with their imputed essence. From the perspective offered by Agamben, judgements regarding purity and impurity can be seen as in part constructing the essence against which they supposedly simply measure phenomena. Agamben's investigations suggest that on occasions when themes of purity or impurity are invoked within Western discourses on subjectivity, the full human subject tends to be placed as relatively pure: neither too close nor too distant from human essence. FollowingWalter Benjamin, he suggests that such a classification gives the full human subject a certain social protection and inviolability, separating relatively pure and protected human life from impure subjectivities unprotected by social or legal conventions.